Efficacy and safety of ferric carboxymaltose for the management of iron deficiency anemia in women - Palaniappan, Narayanan; Sukhadiya, Mehul V. (International Journal of Research in Medical Sciences, 2025)
Iron deficiency anemia (IDA) remains the most common nutritional deficiency across the world with about1in four people suffering from anemia. Iron deficiency anemia spans across the life of a female. Healthy females absorb 5.6% of iron in diet. The efficacy of oral iron is diminished when uptake through the gut is impaired or when iron losses are large and/or continuous (eg, menorrhagia, gastrointestinal bleeding, or post-surgery). Dose-dependent gastrointestinal side effects hinder compliance and result in poor patient compliance in upto 50% of patients. For patients who are diagnosed with IDA during 2nd or 3rd trimesters, intravenous iron replacement therapy (IRT) is recommended. One of the commonly used parenteral iron formulations include ferric carboxymaltose (FCM). Iron supplied as FCM is quickly distributed to different tissues. In randomized trials in pregnant women with IDA, postpartum women with anemia and women with heavy menstrual bleeding, treatment with FCM significantly improved hemoglobin levels compared with oral iron treatment. Ferric carboxymaltose can be used at high doses and allows rapid administration (up to1000 mg in a single dose infused in 15 min). Since FCM is a dextran-free, it does not react with dextran antibodies, thus resulting in a lower risk for hypersensitivity reaction. The novel iron formulation ferric carboxymaltose (FCM) has a better potential for restoring the iron stores. It reduces the dosage frequency which is the chief drawback of parenteral preparations and there is minimal drug related adverse effects. Hence FCM can be the drug of choice for the management of iron deficiency anemia in women.